From metal to paper: validating paper money from Islamic perspective - Sifat, Imtiaz Mohammad; Mohamad, Azhar (Emerald Group Publishing Ltd., 2018)
Purpose – The purpose of this paper is to provide a critical, historical, and legal account and analysis of how money, an inexorable lubricant of all economies, evolved from metallic origins to acceptance in paper form in Muslim traditions. Design/methodology/approach – This paper underlines flaws, points of objections, corollaries and counter-points, and it ends with a thematic discussion on the way forward for Muslim nations with respect to various political and regulatory implications for implementations of potential paper money alternatives Findings – After undergoing experimentation and customary use of various objects as money (such as sea shells, gold, silver, stones, tobacco, etc.), the world has finally settled down by embracing paper money as an official medium of exchange. Originality/value – Paper money also endured many financial crises and initial oppositions to its premise. From an Islamic standpoint, paper money poses certain flaws and limitations that can make it unacceptable from legal perspectives. Keywords Africa, Bimetallism, Shariah, Currency, Murabitun movement, Paper money Paper type Research paper